Annexin A1 involved in the regulation of inflammation and cell signaling pathways - Han, Peng-Fei; Che, Xian-Da; Li, Hong-Zhuo; Gao, Yang-Yang; Wei, Xiao-Chun; Li, Peng-Cui (Chinese journal of traumatology, 2020)
With the deepening of research, proteomics has developed into a science covering the study of all the structural and functional characteristics of proteins and the dynamic change rules. The essence of various biological activities is revealed from the perspectives of the biological structure, functional activity and corresponding regulatory mechanism of proteins by proteomics. Among them, phospholipid-binding protein is one of the hotspots of proteomics, especially annexin A1, which is widely present in various tissues and cells of the body. It has the capability of binding to phospholipid membranes reversibly in a calcium ion dependent manner. In order to provide possible research ideas for researchers, who are interested in this protein, the biological effects of annexin A1, such as inflammatory regulation, cell signal transduction, cell proliferation, differentiation and apoptosis are described in this paper.